COVID-19 tents: specialized triage service, a temporal analysis of the patients' profile - Daniele Brasil; Luciana Julek; Luciane Patrícia Andreani Cabral; Guilherme Arcaro; Mirian Cristina Ribas; Maria Dagmar da Rocha Gaspar; Danielle Bordin (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the change in the clinical-epidemiological profile of patients attended at the specialized triage service for COVID-19 (COVID-19 tent) in the first three months of operation. Methods: Cross-sectional study, with users attended from March 2020 to May 2020 (n=379) at the COVID-19 tent in the city of Ponta Grossa, Paraná. Data collection was retrieved from an electronic form fed by tent professionals, which included sociodemographic characteristics, symptoms, risk factors of exposure, means of search and clinical conduct. Trend tests and chi-square tests were performed. Results: March showed a greater demand (n=197), motivated by mild symptoms and direct search (p<0.05). In the following months, there was a decrease in demand (n=93; n=89), however the search for referrals, ambulances and conditions that required medical attention, observation and hospitalization increased (p<0.05). The search resulting from exposure to risk factors has not changed (p>0.05). Conclusion: the profile has changed over time, reflecting, in the end, severe and critical symptoms, requiring intervention.